Britain's lost revolution? : Jacobite Scotland and French grand strategy, 1701-8 - Daniel, Szechi (Book collections on Project MUSE., 2016)
This book is a frontal attack on an entrenched orthodoxy. Our official, public vision of the early eighteenth century demonises Louis XIV and France and marginalises the Scots Jacobites. Louis is seen as an incorrigibly imperialistic monster and the enemy of liberty and all that is good and progressive. The Jacobite Scots are presented as so foolishly reactionary and dumbly loyal that they were (sadly) incapable of recognising their manifest destiny as the cannon fodder of the first British empire. But what if Louis acted in defence of a nation's liberties and (for whatever reason) sought to r.